Secondary Metabolites From Different Extractives of Stereospermum suaveolens - Begum, Fatema; Haque, Mohammad Rashedul; Nahar, Kazi Sharmin; Rashid, Mohammad Abdur (Dhaka University Journal of Pharmaceutical Sciences, 2015)
The methanol extract of leaves and bark of Stereospermum suaveolens has been subjected to repeated-chromatographic separation and purification processes to isolate the secondary metabolites. A total of seven compounds have been isolated from the plant, which were identified as fridelin (1), ?-sitosterone (stigmast-5- en-3-one) (2), stigmasterol (3), 3,4-dimethoxy cis-caffeic acid (4), 3?-friedelanol (5), ?-amyrone (6) and glyceryl tricaprate (7). The structures of the isolated compounds were elucidated by extensive NMR studies. DOI: http://dx.doi.org/10.3329/dujps.v13i1.21857 Dhaka Univ. J. Pharm. Sci. 13(1): 31-36, 2014 (June)